2006
DOI: 10.18084/1084-7219.11.2.102
|View full text |Cite
|
Sign up to set email alerts
|

Online Versus Classroom-Based Instruction: A Comparative Study of Learning Outcomes in a Diversity Course

Abstract: This study compares the learning outcomes of a traditional, classroom-based course and an online section of the same course on the attitudes and knowledge students have regarding gay men and lesbians. The study was conducted in two sections of an undergraduate social work course entitled lesbian and gay lives. The study found that online and traditional teaching modalities were equally effective in achieving course objectives. Students in both sections had more favorable attitudes towards lesbians and gay men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…These measures have been found to be comparable or better for online students (Cummings, Foels, & Chaffin, 2013;Siebert, Siebert, & Spaulding-Givens, 2006;Wilke & Vinton, 2006). Likewise, the majority of studies examining student satisfaction have revealed either equivalent or, in some cases, superior satisfaction results among students enrolled in the online courses (Banks & Faul, 2007;Faul, Frey, & Barber, 2004;Hylton, 2006;Ligon, Markward, & Yegidis, 1999;Woehle & Quinn, 2009;York, 2008). Student satisfaction has long been considered an important part of a successful Web-based education (Crowell & McCarragher, 2007;Siebert, Siebert, & Spaulding-Givens, 2006;Stocks & Freddolino, 2000).…”
Section: Online Social Work Educationmentioning
confidence: 99%
“…These measures have been found to be comparable or better for online students (Cummings, Foels, & Chaffin, 2013;Siebert, Siebert, & Spaulding-Givens, 2006;Wilke & Vinton, 2006). Likewise, the majority of studies examining student satisfaction have revealed either equivalent or, in some cases, superior satisfaction results among students enrolled in the online courses (Banks & Faul, 2007;Faul, Frey, & Barber, 2004;Hylton, 2006;Ligon, Markward, & Yegidis, 1999;Woehle & Quinn, 2009;York, 2008). Student satisfaction has long been considered an important part of a successful Web-based education (Crowell & McCarragher, 2007;Siebert, Siebert, & Spaulding-Givens, 2006;Stocks & Freddolino, 2000).…”
Section: Online Social Work Educationmentioning
confidence: 99%
“…Students also preferred face-to-face interaction with teachers to online instruction, and almost half (42%) indicated that they did not learn well using the Internet-based approach. Hylton (2006) compared the learning outcomes for students taking two different versions of an undergraduate diversity course. The traditional, 3-hour, classroom-based section and the online section did not differ in their impact on attitudes or knowledge.…”
Section: Research Literature: New Versus Old Teaching Technologiesmentioning
confidence: 99%
“…Hylton (2006) found no differences with regard to the attainment of learning objectives between students in asynchronous and FTF learning environments. Benbunan-Fich and Hiltz (2003) found no significant difference in students' perceptions of learning between asynchronous, FTF, and mixed classroom environments.…”
Section: Learning Environmentsmentioning
confidence: 65%
“…For students in this study, the process of transformation learning took place regardless of learning environment. Perhaps that is not surprising considering earlier work found no difference in both the attainment of learning objective and students' perceptions of learning between asynchronous and FTF learning environments (Benbunan-Fich and Hiltz, 2003;Hylton, 2006).…”
Section: Resultsmentioning
confidence: 85%